METHODS OF IMPLEMENTATION OF THE EUROPEAN CYBERSECURITY SKILLS FRAMEWORK IN THE FORMATION OF THE CONTENT OF THE PROFESSIONAL STANDARD "HEAD OF THE STRUCTURAL UNIT FOR INFORMATION SECURITY AND CYBER DEFENCE" - Yudin, Oleksandr; Yudin, Oleksii; Chernysh, Lesya; Telyushchenko, Valentyna (Science-based technologies, 2024)
The paper analyses the existing methods and best international practices for creating a system of professional standardisation in the field of cybersecurity and information protection. It is shown that at present, a new List of professions has been formed in accordance with the needs of the labour market in the field of cybersecurity and information protection. For the first time in many years, on the initiative of a comprehensive group of specialists at the State Special Communications Service of Ukraine, changes were made and new professions were added to the classifier of professions DK - 003: 2010 in the field of cybersecurity and information protection (Amendments #10, Order of the Ministry of Economy No. 810 dated 25.10.21; Amendments #11, Order of the Ministry of Economy No. 5573 dated 29.12.22). According to the Amendments for 2024, the total number of cybersecurity professions in Ukraine is 27 professions and 46 qualifications. According to the "Classifier of Occupations" DK 003:2010 and in accordance with the best international practices, the said list of occupations was formed on the basis of the implementation of the best international professional standards, namely, taking into account the European Cybersecurity Skills Framework (ECSF ENISA, ECSF role profile). Also, the paper provides conceptual and methodological recommendations for the formation of a basic model of the content of professional standards, namely, the creation of the content of competencies, knowledge, skills and abilities of the professional standard "Head of a structural unit for information security and cyber defence". The material presented is considered with the aim of analysing and providing practical recommendations on methods and procedures for the implementation and development (adaptation to national requirements) of professional standards (hereinafter referred to as PS) and their corresponding qualifications in accordance with the approved Amendments to the National Classifier of Occupations "Classifier of Occupations" DK 003:2010 (Amendments No. 10, Order of the Ministry of Economy No. 810 of 25.10.2021; Amendments No. 11, Order of the Ministry of Economy No. 5573 of 29.12.2022). This material presents an example in accordance with the European Cybersecurity Skills Framework (ECSF) and in accordance with the Classifier of Occupations DK 003:2010 and the National Qualifications Framework of Ukraine.